PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUKAN MEDIA GAMBAR PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS IV SD INPRES JONGAYA - Annisa; Nur Anisa Mansur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is in the form of classroom action research conducted at IV SD Inpres Jongaya. This research aims to determine the improvement in student learning outcomes in Class IV Mathematics at SD Inpres Jongaya, through the application of the problem based learning model using puzzle image media. This type of research is classroom action research. Student learning outcomes in cycle I with an average score of 57.14 in the incomplete category with a percentage of 33% in the incomplete category. Observations on the implementation of learning in the first cycle were 94% of the category was carried out well, while observations of student activities in the first cycle were 88% of the category was carried out well. It increased in cycle II with an average learning outcome score of 82.01 in the complete category with a percentage of 81% in the complete category. Observation of learning implementation in cycle II with 95% of the category being well implemented and observation of student activities in cycle II with 95% of the category being well implemented. Keywords: Problem Based Learning (PBL), Puzzele Image Media, Matematics Learning,